Digital Citizenship Education for Good Governance: A Character-Based Approach Rooted in Local Wisdom - Ardiansyah, Suriadi; Yorman, Yorman; Rassyi, Sultan Fakhrur (Innovations in Pedagogy and Technology, 2025)
The rapid digital revolution has reshaped civic life and governance, demanding transparency, participation, and ethical responsibility. Within this context, digital citizenship education (DCE) emerges as a crucial pedagogical framework for cultivating citizens who are technologically proficient, morally grounded, and culturally responsive. This study aims to construct a conceptual model of character-based digital citizenship education rooted in Indonesian local wisdom as a foundation for good governance. Employing a qualitative approach through a critical literature review, academic sources were systematically selected from Scopus, WoS, and other reputable databases using inclusion criteria that emphasized relevance to DCE, character education, and local cultural values. Thematic analysis was conducted to identify key patterns and synthesize integrative perspectives. The findings reveal that integrating global principles of digital ethics, civic participation, and digital literacy with local values such as mutual cooperation, deliberation for consensus, and cultural politeness strengthens anti-corruption culture, civic responsibility, and democratic resilience. Furthermore, this character-based and culturally rooted DCE framework advances both theory and practice by linking digital transformation with governance reform in developing contexts. The study contributes to curriculum innovation, education policy design, and the achievement of SDGs 4.7 and 16, positioning DCE not merely as technical training but as a transformative process for building inclusive and ethical digital societies.